2018
DOI: 10.1002/stem.2764
|View full text |Cite
|
Sign up to set email alerts
|

Polycystin-2 Plays an Essential Role in Glucose Starvation-Induced Autophagy in Human Embryonic Stem Cell-Derived Cardiomyocytes

Abstract: Autophagy is a process essential for cell survival under stress condition. The patients with autosomal dominant polycystic kidney disease, which is caused by polycystin-1 or polycystin-2 (PKD2) mutation, display cardiovascular abnormalities and dysregulation in autophagy. However, it is unclear whether PKD2 plays a role in autophagy. In the present study, we explored the functional role of PKD2 in autophagy and apoptosis in human embryonic stem cell-derived cardiomyocytes. HES2 hESC line-derived cardiomyocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
0
18
1
Order By: Relevance
“…Autophagy impairment has been proposed to play a crucial role in the pathogenesis of ADPKD by modulating cell proliferation [42]. A defect in autophagy may predispose cyst lining cells to apoptosis and promote cyst formation in ADPKD [43]. However, the degree of autophagy impairment in different stages of cyst development, such as early versus late, could be different [13].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy impairment has been proposed to play a crucial role in the pathogenesis of ADPKD by modulating cell proliferation [42]. A defect in autophagy may predispose cyst lining cells to apoptosis and promote cyst formation in ADPKD [43]. However, the degree of autophagy impairment in different stages of cyst development, such as early versus late, could be different [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that PC2 stimulates autophagy in a variety of cell types, including renal epithelial cells, as well as cardiomyocytes, involving both the primary cilium and intracellular calcium stores 2831 . LC3 is the most widely used autophagosome marker because the amount of LC3 II (conjugated to phosphatidylethanolamine) reflects the number of autophagosomes 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that there is evidence for the link between ER stress and the inflammatory cytokine activation that IL‐1β decreased significantly when pretreated human cells were treated with 4‐PBA or TUDCA under LPS treatment (Liong & Lappas, ). Previous studies reported that activated autophagy in the cell can lead to several responses, such as a covered self‐degradative catabolic process to degrade and recycle damaged organelles, and that activated autophagy coordinates programmed cell death but also has a protective role against apoptosis under stress conditions (Lu et al, ; Wang et al, ). LC3 plays a critical role in autophagosomes and is a marker of autophagy activation (Tanida, Ueno & Kominami, ).…”
Section: Discussionmentioning
confidence: 99%